Joint Quran Recitation Activities to Improve the Quality of Worship During Ramadan at the Al-Hidayah Tambak Sumur Sidoarjo Musholla - Sirojuddin Abror; Wanda Citra Dewi; Nur Fais Zalillah (Abdimas Indonesian Journal, 2025)
Religious education based on the Qur’an plays a strategic role in shaping individuals’ spiritual, cognitive, and social development. However, in the Tambak Sumur community, Sidoarjo Regency, a gap remains between strong religious traditions and the depth of Qur’anic literacy, particularly among children and adolescents. This condition is further exacerbated by technological developments that shift religious activities away from mosques and prayer rooms. Therefore, this PKM activity aimed to improve the quality of worship and Qur’anic literacy through a joint Qur’an recitation program at the Al-Hidayah Tambak Sumur Musholla during the month of Ramadan. This PKM activity employed the Asset-Based Community Development (ABCD) approach, which emphasizes the identification and utilization of existing community assets, including religious facilities, social solidarity, and the role of local religious leaders. The results showed that the joint recitation program was well received and generated high enthusiasm among participants, especially children. The activity contributed to improving participants’ Qur’an reading skills in accordance with tajwid rules, strengthening motivation to learn, and fostering mutual learning and social interaction. In conclusion, the joint Qur’an recitation PKM program proved effective in improving Qur’anic literacy, enhancing the quality of worship during Ramadan, and fostering a more religious, harmonious, and socially cohesive community. The activity is recommended to be continued on a regular basis to ensure sustainable impact.